Inspiratory muscle fatigue affects latissimus dorsi but not pectoralis major activity during arms only front crawl sprinting - Lomax, M.; Tasker, L.; Bostanci, O. (The Journal of Strength and Conditioning Research, 2014)
The purpose of this study was to determine whether inspiratory muscle fatigue (IMF) affects the muscle activity of the latissimus dorsi and pectoralis major during maximal arms only front crawl swimming. Eight collegiate swimmers were recruited to perform 2 maximal 20-second arms only front crawl sprints in a swimming flume. Both sprints were performed on the same day, and IMF was induced 30 minutes after the first (control) sprint. Maximal inspiratory and expiratory mouth pressures (PImax and PEmax, respectively) were measured before and after each sprint. The median frequency (MDF) of the electromyographic signal burst was recorded from the latissimus dorsi and pectoralis major during each 20-second sprint along with stroke rate and breathing frequency. Median frequency was assessed in absolute units (Hz) and then referenced to the start of the control sprint for normalization. After IMF inducement, stroke rate increased from 56 ± 4 to 59 ± 5 cycles per minute, and latissimus dorsi MDF fell from 67 ± 11 Hz at the start of the sprint to 61 ± 9 Hz at the end. No change was observed in the MDF of the latissimus dorsi during the control sprint. Conversely, the MDF of the pectoralis major shifted to lower frequencies during both sprints but was unaffected by IMF. As the latter induced fatigue in the latissimus dorsi, which was not otherwise apparent during maximal arms only control sprinting, the presence of IMF affects the activity of the latissimus dorsi during front crawl sprinting.